Determining the rational energy level for processing environments of different structures - Nazarenko, Ivan; Dedov, Oleg; Bernyk, Iryna; Zapryvoda, Andrii; Ruchynskyi, Mykola; Bondarenko, Andrii (Eastern-European Journal of Enterprise Technologies, 2025)
Vibration processing underlies many technological processes in various sectors of the national economy. The object of the study is a single common wave process of motion of the system, and the subject is the parameters and modes that provide a rational level of energy. At the same time, attention is focused on the use of energy-saving technologies. Most processes use energy-consuming technologies and equipment, the calculations of which are based on the application of formulas for determining energy on discrete and empirical dependencies. Such approaches do not reveal the essence of the material processing processes and cannot accurately estimate energy costs. This problem is solved in the work by determining the parameters and modes based on the conditions for implementing the synergy of the “vibration exciter – processing medium” system. This is the peculiarity and difference of the obtained research results. Discrete-continuous models have been developed taking into account the rheological properties of the media, and analytical solutions and experimental studies have allowed to determine the parameters of low-frequency and high-frequency actions on the processing medium. The work uses a method by which the combination of frequency and amplitude of vibrations determines the intensity of the vibration effect on the processing environment. The resistance of the technological environment to the movement of the working body of the vibration exciter, which consisted of inertial, elastic and dissipative parts, was determined. The study determined the qualitative and quantitative picture of the change in energy dissipation in specific materials and environments under different laws of their loading and processing. The energy level for processing technological environments in low-frequency and high-frequency modes was determined. The research methodology and analytical dependence of energy determination can be used for various environments under load